2023
DOI: 10.1002/ajb2.16127
|View full text |Cite
|
Sign up to set email alerts
|

A trait‐based approach to determining principles of plant biogeography

Abstract: Lineage-specific traits determine how plants interact with their surrounding environment. Unrelated species may evolve similar phenotypic characteristics to tolerate, persist in, and invade environments with certain characteristics, resulting in some traits becoming relatively more common in certain types of habitats. Analyses of these general patterns of geographical trait distribution have led to the proposal of general principles to explain how plants diversify in space over time. Trait-environment correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 92 publications
(89 reference statements)
1
10
0
Order By: Relevance
“…Our results reinforced the well‐known pattern of geographic biases in scientific efforts (Clarke et al, 2017 ; Culumber et al, 2019 ; Nuñez et al, 2021 ; Vasconcelos, 2023 ; Zuk, 2016 ). Previous studies on functional traits with specific taxa (Luiza‐Andrade et al, 2017 ) or themes (Hevia et al, 2017 ) already reported the predominance of studies conducted in Europe and North America.…”
Section: Trends Gaps and Biases In The Study Of Animal Functional Traitssupporting
confidence: 88%
See 1 more Smart Citation
“…Our results reinforced the well‐known pattern of geographic biases in scientific efforts (Clarke et al, 2017 ; Culumber et al, 2019 ; Nuñez et al, 2021 ; Vasconcelos, 2023 ; Zuk, 2016 ). Previous studies on functional traits with specific taxa (Luiza‐Andrade et al, 2017 ) or themes (Hevia et al, 2017 ) already reported the predominance of studies conducted in Europe and North America.…”
Section: Trends Gaps and Biases In The Study Of Animal Functional Traitssupporting
confidence: 88%
“…Ecology has strong biases toward specific taxonomic groups (plants, birds) and geographical regions (temperate), which goes beyond studies with functional traits (Clarke et al, 2017 ; Culumber et al, 2019 ; Vasconcelos, 2023 ; Zuk, 2016 ). For example, almost half of the studies use vertebrates as model organisms.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…For example, in comparative biology, studies examining large phylogenies usually have little power to determine specific mechanisms underpinning evolutionary patterns (Donoghue & Edwards, 2019), while small‐scale studies of specific clades, for various reasons, are often limited in their ability to explain broad evolutionary patterns (Beaulieu & O'Meara, 2018, 2019). The multi‐clade approach we used for this work, which allowed us to examine broad patterns as well as clade‐specific patterns, aims to combine the advantages of both large‐ and small‐scale studies (Vasconcelos, 2023). Due to their advantages, multi‐clade studies have recently become popular in comparative biology (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting diversification rates of lineages with distinct climbing mechanisms can contribute to the challenging, yet fundamental, question in evolutionary biology: why have some groups diversified more than others (Magallón & Sanderson, 2001; Wiens & Donoghue, 2004; Onstein, 2019)? Studies of this kind have been hampered by the lack of basic data on traits, phylogenetic relationships, and geographical distribution from the areas where climbing plants have diversified the most, that is, the tropics (Gentry, 1991; Grace et al ., 2021; Vasconcelos, 2023).…”
Section: Introductionmentioning
confidence: 99%